INEXTENSIBLE FLOWS OF b-TANGENT DEVELOPABLE SURFACES OF BIHARMONIC NEW TYPE b-SLANT HELICES ACCORDING TO BISHOP FRAME IN THE SOL SPACE Sol3 - Korpinar, Talat; Turhan, Essin (Editura Bibliotheca-Bibliotheca Publ House, 2012)
In this paper, we study inextensible flows of b - tangent developable surfaces of biharmonic new type b - slant helix in the Sol(3). We obtain partial differential equation for - tangent developable surfaces of biharmonic new type b - slant helix in terms of their Bishop curvatures. Finally, we find explicit parametric equations one- parameter family of the b - tangent developable surface of a unit speed non- geodesic biharmonic new type b - slant helix in the Sol(3.).
Keywords: New type b-slant helix; Sol Space; Curvature; Torsion